Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/pmic.201900092
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis Reveals that Odoroside A Triggers G2/M Arrest and Apoptosis in Colorectal Carcinoma Through ROS‐p53 Pathway

Abstract: Odoroside A (OA) is an active ingredient extracted from the leaves of Nerium oleander Linn. (Apocynaceae). This study aims to examine the anticancer bioactivity of OA against CRC cells and to investigate the action mechanisms involved. As a result, OA can significantly inhibit cellular ability and induce apoptosis of CRC cells in a concentration‐dependent manner without any obvious cytotoxicity in normal colorectal epithelial cells. Then, quantitative proteomics combined with bioinformatics is adopted to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…An increased understanding of the role of ROS shows that ROS are not only metabolic byproducts but also signaling molecules [7,8]. Excess ROS could activate several injury-producing pathways, such as the nuclear factor-kb (NF-κb) inflammatory and p53 apoptotic pathways [9,10]. The transcription factor and tumor suppressor p53 is closely related to DNA repair, cellular stress response, and cell cycle control [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…An increased understanding of the role of ROS shows that ROS are not only metabolic byproducts but also signaling molecules [7,8]. Excess ROS could activate several injury-producing pathways, such as the nuclear factor-kb (NF-κb) inflammatory and p53 apoptotic pathways [9,10]. The transcription factor and tumor suppressor p53 is closely related to DNA repair, cellular stress response, and cell cycle control [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also shown that the function of p53 is closely related to ROS [58]. ROS not only regulates the activity of p53, but also participates in p53-dependent apoptosis [59]. Therefore, CCM@MSNs-ISOIM may induce the production of high levels of ROS and mediate G2/M block in NHL, which leads to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also shown that the function of p53 is closely related to ROS [72]. ROS not only regulates the activity of p53, but also participates in p53-dependent apoptosis [73]. Therefore, CCM@MSNs-ISOIM may induce the production of high levels of ROS and mediate G2/M block in NHL, which leads to apoptosis.…”
Section: Discussionmentioning
confidence: 99%